The Effect of Viscosity on the Temperature of Ae Star Disks - R. Anusha; T. A. A. Sigut (Galaxies)
This study explores the impact of viscous heating on decretion disks around Classical Ae (CAe) stars, with a focus on modeling the disk’s thermal structure. While photoionization is the dominant heating mechanism, viscous dissipation can play an important role in shaping the disk temperature, particularly for cooler CAe subtypes. Our models incorporate viscosity-driven heating and predict that shear heating has a negligible effect for early A-type stars (A0–A1), but it becomes increasingly significant for later spectral types, especially as the viscosity parameter (<semantics>α</semantics>) increases. This heating also influences the strength of H<semantics>α</semantics> emission. Furthermore, our models predict a sharp decline in the number of emission-line stars beyond spectral type A2, a trend observed in CAe populations. However, for sufficiently high <semantics>α</semantics> values (≥0.3), a higher fraction of emission-line objects is expected even among later subtypes, such as A5, despite the lack of well-characterized CAe stars observed beyond the spectral type A4.